Paradise revisited: Images of the first woman in the poetry of Joy Kogawa and the fiction of Thomas King - Filipczak, Dorota (Adam Mickiewicz University, 2007)
The article offers a comparative analysis of a poem by Joy Kogawa entitled A song of Lilith, and the chosen texts by Thomas King, namely his short-story “One good story, that one” and his novel Green grass, running water. Despite being rooted in their respective cultures, these two Canadian writers are interested in the Book of Genesis. Kogawa, of Japanese origin, and King, of Cherokee and Greek origin, rewrite the story of the first woman by deconstructing the images of femininity from Old and New Testaments. King’s and Kogawa’s interpretations communicate much about the authors’ status within the Canadian mainstream.